Cultura letrada e caminhos da memória: intelectuais, leitura, imprensa e memória na Zona Norte do Ceará (1870-1890, 1907-1932, 1984-2003) - Lima, Jorge Luiz Ferreira de (2018)
The present work seeks to analyze the present conflicts in the construction of an organizing memory for the cities of the northern area of Ceará. We are interested in this memory of its emphasis on the action of intellectuals and the desire to attribute the status of "intellectual city" to the cities in question. Obviously, such a memory failed to impose silence on the divergent memories that challenged it’s hegemony. The main internal split of this memory emerged along with a new category within the intellectual field: the journalists. This process can be perceived from the analysis of the professional and social trajectories of Vicente Loyola and Deolindo Barreto Lima, two journalists whose memories constituted a challenge to that intellectual memory in Sobral. The spatial clipping contemplates the northwestern portion of Ceará, with the epicenter of the city of Sobral, where this memory focused on the intellectuals was felt more intensely, and can be seen in the newspapers, literature and, more recently, in the patrimonialisation process. To do so, we analyze two previous processes: the diffusion of the book and the reading, anchored to a project of diffusion of the instruction represented by the offices of reading, when we report the years of 1870 to 1900; the consolidation of the press as a space for the professionalization of intellectual work and the conflicts that emerged in this process that included diverse discourses and trajectories, including the interval between 1907 and 1932; and, finally, the period from 1984 to 2015, when the process of patrimonalization began, commemorating the centenary of the birth of the journalist Deolindo Barreto Lima, passing through the historic sites of Sobral and Viçosa do Ceará and arriving at the days where these cities as well as others in the northern part of this state seek to consolidate them as important points in the process of internalization of tourism and initiatives of a governmental nature in the scope of cultural promotion. This work is part of a set of studies developed by the Group of Studies and Research in Patrimony and Memory - GEPPM/UFC/CNPq.